Making of Nooses: Accentuating Vulnerability, Resilience, and Violence in K.R. Meera’s Hangwoman - Pragya Dev; Binod Mishra (Asiatic: IIUM Journal of English Language and Literature, 2023)
Contemporary descriptions of female embodiment are rife with images of violence, domination, and subjugation. Often bracketed as vulnerable, women are constantly subjected to patriarchal and gendered violence. Vulnerability, however, is an ontological condition of humanity and can yield multifarious responses – abuse, love, disarray, violence, generosity, and contempt – making human life precarious. This precariousness, when situated in the Indian context, exposes humans to varied practices of violence enmeshed in vicious systems of caste, class, region, and religion as demonstrated in K. R. Meera’s Hangwoman (2014). Owing to their centuries-old lineage of hangmen, Grddha Mullicks began making nooses right away in their mother’s wombs. Chetna, the first hangwoman in her family, is staged as the successor to her familial duty to the Nation only because of her brother’s tragic amputation of limbs. Subjected to a shrewd media lens and patriarchal manipulation, the struggle of constructing a new-feminist-styled ‘angel of the house’ depicted in the novel whirls poignant questions to corporeal vulnerability. This article scrutinises the societal treatment of vulnerability and explores physical, interpersonal, and epistemic violence haunting the book’s pages. It further adds nuances to the engagement of media and identity while examining the precarity of the novel’s characters.